INOVASI TEKNOLOGI PENGOLAHAN LIMBAH JAGUNG GUNA MENINGKATKAN EKONOMI KREATIF PADA KELOMPOK TANI - Fitria Rahmadayanti; Febriansyah; Vike Iteridi (Fakultas Pertanian, 2025)
This community service activity was carried out in Pagar Kaya Village, which is one of the corn producing centers in the Pagar Alam area and Lahat Regency, South Sumatra. The abundance of unutilized corn cob waste causes environmental and economic problems. The purpose of this activity is to empower farmer groups to have the skills to process corn waste into products with sales value, increase entrepreneurial insight, and strengthen digital marketing through training and mentoring. The activity methods include socialization and training in briquette making, mentoring in the packaging and marketing process, and the application of simple technology to increase production efficiency. The output targets of this PKM activity are 1) increasing the knowledge of farmer groups about making briquettes, 2) Improving the skills of farmer groups, 3) Scientific publications in Sinta-accredited national journals with published status, 4) Publications in print/electronic media with published status, 5) Videos of activities shared on social media. The results showed that the partners were able to independently produce briquettes, package the products under the